Targeting physical activity promotion in general practice: Characteristics of inactive patients and willingness to change - Sánchez-Pinilla Ricardo; Torcal Jesús; Sánchez Alvaro; Grandes Gonzalo; Lizarraga Kepa; Serra Javier (BMC, 2008)
Abstract Background Counselling in routine general practice to promote physical activity (PA) is advocated, but inadequate evidence is available to support this intervention, and its sustainable implementation over time is difficult. Objectives To describe the characteristics of physically inactive adults visiting GPs and the factors associated with their willingness to change PA. Methods A cross-sectional analysis of 4317 Spanish people aged 20-80 years, selected by systematic sampling among those attending 56 public primary health care practices identified as inactive by their GPs in 2003. PA (7-day PAR), PA stage of change, health-related quality of life (SF-36), cardiovascular risk factors, and social and demographic characteristics were measured. Multivariate mixed effects ordinal logistic models were adjusted to identify factors associated with motivational readiness to change. Results At least 70% (95% CI: 67.6% to 72.8%) of patients assessed by GPs did not achieve minimal PA recommendations. In addition, 85% (95% CI: 83% to 86.3%) had at least an additional cardiovascular risk factor. Only 30% (95% CI: 25.8% to 33.5%) were prepared for or attempting a change. A younger age; retirement or work at home; higher education and social class levels; obesity; and hypertension were associated with a higher motivational readiness to change (p < 0.05). Conclusion The overburden that would result from counselling such a high proportion of inactive primary care patients justifies a targeted strategy for PA promotion in family practice. Selection of a target population based on readiness to change, the combination of risk factors and socio-demographic characteristics of patients is suggested in order to prioritise promotion efforts.